Pemanfaatan Media Visual dalam Memahami Sesonggan pada Siswa SMP Taman Rama Jimbaran Tahun Pelajaran 2022/2023 - Ida Ayu Putu Asti Pratiwi; Maria Osmunda Eawea Monny (Journal on Education, 2023)
The purpose of this research is to improve students’ understanding on sesonggan (proverb) of Balinese language. The implementation of visual media to improve understanding of the students of Taman Rama Junior High School on sesonggan using Constructivism theory and the media is visual media. Almost all groups can use the visual media properly based on the performance rubrics. The impact of visual media to improve students’ understanding can be seen through their quiz’ results which shown that the mean out 24 students is 98 (excellent). Students’ interest about the topics was 87.5% has good response about visual media and it can be seen through their answers which stated that they were happy, not boring, attractive, easy and practical.